A precise embedded curvature sensor module for soft-bodied robots - Ozel, Selim; Keskin, Nehir A.; Khea, Darien; Onal, Cagdas D. (Sensors and actuators. A. Physical., 2015)
•Robust and precise curvature feedback with rapid response for soft-bodied robots.•Integrated measurement of kinematic configuration for soft-bodied arms and mobile robots composed of soft bending segments.•A custom test platform for soft-bodied curvature sensors. As an emerging field, soft-bodied robots require profoundly different approaches to sensing and actuation compared to their rigid-bodied counterparts. Electro-mechanical design, fabrication, and operational challenges due to material elasticity significantly complicate embedded, modular and precise proprioceptive feedback. This work presents a novel curvature sensor module to address the unique soft robotic specifications. The proposed device utilizes a magnet and an electronic Hall effect sensing component to accurately measure curvatures on a soft-bodied bending segment on a flexible circuit board, ensuring contact-free sensing. We verify performance of sensor modules on static and dynamic bending deformations based on a single initial calibration step. To the best of our knowledge, the presented device is the first modular and integrated soft-bodied sensor design that is demonstrated to be accurate up to 7.5Hz with a root mean square error of 0.023cm−1 between measured and actual curvature without filtering out the intrinsic noise, and available for use with soft-bodied kinematic bending chains.